The Synthesis of Self-Efficacy of Academic Resilience Capacity (SEARC) as the Implication of Self-Efficacy Contribution to Student Academic - Fatia, Azhariah; Alfaiz, Alfaiz; Yuzarion, Yuzarion; Julius, Andre; Hidayat Rafiola, Ryan; Singgih Sendayu, Fendahapsari; Valdez, Anabelie V.; Juliawati, Dosi (Tarbawi : Jurnal Ilmu Pendidikan, 2022)
Many students in the educational process need more resilience. This research aims to determine the academic resilience of students' self-efficacy aspects, such as mastery experience, vicarious experience, social persuasion, and emotional state. It also aims to synthesize a framework for modifying students’ academic behavior, namely Self-Efficacy of Academic Resilience Capacity (SEARC). A quantitative approach with regression and literature analyses was used to develop a synthesis framework based on the field findings. The random sampling method was used to collect data on students' self-efficacy. The instrument used in this research was the Academic Self-Efficacy Scale (ASES) developed by Alfaiz with a 0.898 reliability. The collected data were analyzed descriptively and regression analysis was used to test the hypothesis. The results showed that mastery experience, vicarious experience, and emotional state significantly increase students’ resilience but social persuasion is insignificant when viewed partially. It implies that self-efficacy ability contributes to academic resilience.